50 years of feeding the world: How CGIAR agricultural research benefits the United States and the world - CGIAR System Organization; Farm Journal Foundation (CGIAR System Organization, 2019)
U.S. agriculture benefits directly and indirectly from research conducted through international projects, including those led by CGIAR. Recent CGIAR research has provided improved pest, disease, or fungal resistance to seed varieties used by U.S. producers of pulse crops (such as peas and beans), peanuts, corn, sorghum, tomatoes, and other specialty crops.